Simmons, Betty. New Perlican Photograph of five men walking the street. - Barrett, Terra
A photograph of five members of the SUF (Society of United Fishermen) Lodge: Walt Smith, Herb George, and three others. They are seen in their SUF regalia walking down the street. Dr. Phil Warren's former house and stores in background.